Theatre in Cyprus (19th Century – 1959) - Katsouris, Yiannis (Études helléniques / Hellenic Studies, 2007)
The author of this article focuses on the term “Cypriot literature” and points out its prevalence on other terms used from time to time. He argues in favour of the term Cypriot literature because such terms as Greek literature of Cyprus and modern Greek literature of Cyprus make up a redundant and dangerous grammatological terminology that could exclude or eliminate the “Cypriot” dimension from various expressions of Cypriot life.